Development, characterization and solubility study of solid dispersions of azithromycin dihydrate by solvent evaporation method - S C Arora; P K Sharma; Raghuveer Irchhaiya; Anurag Khatkar; Neeraj Singh; Jagbir Gagoria (Wolters Kluwer Medknow Publications, 2010)
Azithromycin Dihydrate (Poorly water soluble drug), when prepared as solid dispersion showed improved solubility and dissolution. So the main purpose of this investigation was to increase the solubility and dissolution rate of Azithromycin Dihydrate by the preparation of its solid dispersion with urea using solvent evaporation method. Physical mixtures and solid dispersions of Azithromycin Dihydrate were prepared by using urea as water-soluble carrier in various proportions (1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7 by weight), by employing solvent evaporation method. The drug release profile was studied and it was found that the dissolution rate and the dissolution parameters of the drug from the physical mixture as well as solid dispersion were higher than those of the intact drug. FT- IR spectra revealed no chemical incompatibility between drug and urea. Drug-polymer interactions were investigated using differential scanning calorimetry (DSC) and Powder X-Ray Diffraction (PXRD).